ANALISIS YURIDIS PEMBATALAN PUTUSAN BAPMI OLEH PUTUSAN PENGADILAN (STUDI PERKARA NOMOR 513/PDT.G-ARB/2012/PN.JKT.PST) - Yohanna Petresia; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Settlement of business disputes be an option for the parties to the dispute are usually used method of dispute resolution through alternative dispute resolution. Choice of dispute resolution in the capital market conducted litigation in general through the arbitration institution Indonesian Capital Market Arbitration Board (BAPMI). BAPMI arbitration decision issued BAPMI-004 / ARB-03 / VIII / 2011 on the application submitted by PT Bank Permata. BAPMI verdict obliging PT Nikko Securities to replace most of the payments made by PT Bank Permata to investors. However, PT Nikko Securities filed a cancellation decision BAPMI the Central Jakarta District Court by reason of deception in BAPMI decision. BAPMI verdict is final, binding and must be implemented immediately canceled by Court decision No. 513 / PDT.G-ARB / 2012 / PN.JKT.PST.This type of research can be classified into types of normative legal research is research that emphasizes the literature data, cover the entire legislation relating to the object of research. Source of data used is primary data, secondary data and data tertiary. Analysis of the data used in this study is qualitative.BAPMI ruling has the force of law, as stated in Article 48 of the Decree of the Indonesian Capital Market Arbitration Board Number: Kep-02 / BAPMI / 11.2009 of the Rules and Events Indonesian Capital Market Arbitration Board. The head of the written decision BAPMI "SAKE OF JUSTICE UNDER THE ONE ALMIGHTY GOD" which means decision executorial BAPMI have legal force and are binding on the parties. District Court Judge ruled Court No. 513 / PDT.G-ARB / 2012 / PN.JKT.PST related cancellation BAPMI decision. Decision handed down by the judge is not based on proof of their ruse conducted by BAPMI and PT. Bank Permata Tbk. Elucidation of Article 70 of Law Arbitration stated that in order to be able to say meets the requirements as stated in Article 70 of Law Arbitration, the need for advance ruling which stated the presence / absence of the fraudulent action.From the research, there are two basic problems that can be concluded, first, the decision BAPMI already have legal force. Second, evidence has been the fulfillment of the elements of fraud are not carried out by a judge. Advice, First, the arbitration award is final and binding with legal force by the parties should be implemented immediately. The judge can carry out his duties by ordering the execution of the arbitral award is registered to the court. Second, the trial judge should carry out the cancellation of arbitration in accordance with the Civil Procedure Code, that the cancellation of arbitral awards especially BAPMI decision is consistent with the rule of law.Keywords: BAPMI - Arbitration - Decision